2008
DOI: 10.1086/528677
|View full text |Cite
|
Sign up to set email alerts
|

Identifying the Rotation Rate and the Presence of Dynamic Weather on Extrasolar Earth‐like Planets from Photometric Observations

Abstract: With the recent discoveries of hundreds of extrasolar planets, the search for planets like Earth and life in the universe is quickly gaining momentum. In the future, large space observatories could directly detect the light scattered from rocky planets, but they would not be able to spatially resolve a planet's surface. Using reflectance models and real cloud data from satellite observations, here we show that, despite Earth's dynamic weather patterns, the light scattered by the Earth to a hypothetical distant… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
126
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
2
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 123 publications
(129 citation statements)
references
References 27 publications
3
126
0
Order By: Relevance
“…The variability of the visible light curve along one complete orbit indicates variations of the surface albedo under a cloud-free sky and thus could be used to estimate the rotation periods of the planet. However, in the presence of clouds and atmospheric variability, the ability of accurately retrieving the rotation period is difficult, unless the time evolution of the cloud patterns correlates with the rotation period (Palle et al 2008). Based on our results, we expect that determining the rotation period from photometric light curves along one diurnal orbit would be more successful for planets with long rotation periods, because of small variability in the properties of clouds at a given time of the day.…”
Section: Discussionmentioning
confidence: 99%
“…The variability of the visible light curve along one complete orbit indicates variations of the surface albedo under a cloud-free sky and thus could be used to estimate the rotation periods of the planet. However, in the presence of clouds and atmospheric variability, the ability of accurately retrieving the rotation period is difficult, unless the time evolution of the cloud patterns correlates with the rotation period (Palle et al 2008). Based on our results, we expect that determining the rotation period from photometric light curves along one diurnal orbit would be more successful for planets with long rotation periods, because of small variability in the properties of clouds at a given time of the day.…”
Section: Discussionmentioning
confidence: 99%
“…Several aspects of characterizing habitable worlds using orbital photometry have been studied: the effect of the planet's obliquity (Gaidos & Williams 2004) and eccentricity (Cowan et al 2012), the presence of a moon (Selsis 2004;Moskovitz et al 2009), and the rotation period in the visible (Ford et al 2001;Pallé et al 2008) and infrared (Gómez-Leal et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…However, Pallé et al (2008) demonstrated that if sufficient signal to noise can be obtained, it is possible to detect both the presence of continents and the clouds. In any case, our aim here is to characterize the photometric variability of both components combined.…”
Section: Light Curve Reconstructionsmentioning
confidence: 99%
“…Several authors have also attempted to model the diurnal photometric variability on an Earth-like planet (Ford et al 2001;Tinetti et al 2006aTinetti et al , 2006bFujii et al 2010), while other authors such as Woolf et al (2002), Arnold et al (2002), Seager et al (2005, and Montañés-Rodríguez et al (2005 have attempted to measure the characteristics of the reflected spectrum and the enhancement of Earth's reflectance at 700 nm due to vegetation. In addition, Pallé et al (2008) determined that the light scattered by the Earth as a function of time contains sufficient information, even with the presence of clouds, to accurately measure Earth's rotation period. Even crude reconstruction of the continental distribution could be attempted given sufficient signal-to-noise observations (Cowan et al 2009;Oakley & Cash 2009).…”
Section: Introductionmentioning
confidence: 99%